Solitary angiokeratoma of tongue: A case report and review of the literature - K Santhosh Kumar; GVV Giri; Deepak A Pandyan; Abinaya Subramanian; Raina Basu (Wolters Kluwer Medknow Publications, 2018)
Angiokeratoma is a benign cutaneous lesion of capillaries. It is characterized by large dilated blood vessels in the superficial dermis and hyperkeratosis of extremities. It is mostly seen in generalized form affecting the extremity of the body, but we report this case of solitary angiokeratoma of the tongue which is a very rare type.